From Princess to Heroin - the Female Character's Transformation into Hero in the Movie Moana: An Ocean of Adventures - Louzada Ferreira De Morais, Guilherme Augusto [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2018)
Based on Campbell (1997), we will demonstrate how the female character Moana, from the movie Moana, by Disney, embarks on the hero's journey. In addition, we will see that the character leaves the archetypal pattern figure of the Maiden/Princess and assumes the Hero's archetype, since she has many of the elements necessary to compose it, as described by Randazzo (1996) and Mazucchi-Saes (2005). Thus, we will verify that, for being a heroine, and not a princess, Moana breaks many stereotypes (BONNICI, 2007) that the patriarchal system idealized for a woman and, consequently, for her representation in arts. Moana is a reflection of the feminist movement, and she shows that any woman can be a hero.
Keywords: Campbell; Disney; Feminism; Heroine; Moana; Princess